Numerical analysis of the impacts of rainfall on permafrost-related slope stability on the Qinghai–Tibet Plateau - Junming Hao; Peiqian Jia; Tonghua Wu; Wangping Li; Jie Chen; Xiaohui Yang; Xiaodong Wu; Guojie Hu; Kai Cui; Mingli Zhang (Journal of Hydrology: Regional Studies, 2023)
Study region: This study interrogates a landslide in ice-rich permafrost region in the Eastern Qinghai–Tibet Plateau, China. Study focus: Climate warming has increased the frequency and intensity of rainfall events, changing hydrothermal processes and the soil mechanical properties, thus affecting slope stability in permafrost region. The purpose of this paper is to elucidate the variations in soil volumetric water content (VWC) which may influence the mechanical properties of unstable slopes in ice-rich permafrost region under different rainfall conditions. New hydrological insights for the region: This paper integrates the rainfall infiltration boundary conditions and Mohr–Coulomb criterion into a thermo–hydro–mechanical (THM) model and analyzes a landslide case in the permafrost regions. The results show that the THM model can effectively account for the impacts of VWC variation under different rainfall conditions. The influence of rainfall on the VWC diminishes as depth increases, with a more pronounced effect observed at depths less than 1 m. At depths exceeding 1 m, the impact is relatively minor. Under the condition of low-intensity, long-duration rainfall, with accumulated precipitation exceeding 60 mm, the cohesion and internal friction angle decrease to 4.2kPa and 8.1°, respectively, with a deep-layer integral slippage. In contrast, under the condition of high-intensity, short-term rainfall, the accumulated rainfall exceeds 75 mm and the internal friction angle decreases from 39° to 26°, with shallow-layer slippage. The results add on to our understanding engineering problems and periglacial geomorphic processes under the influence of climate warming.